(untitled) (Iter, 2022)
The author starts from the definition o f truth as ’adaequatio intellectus ad rem’. Where ’intellectus’ is understood as ’logos’, ’res’ as the thing itself, upon which falls the saying of the ’logos’, and ’adequatio’ as the "coincidence " or "equating" of that which is expressed in a propos al with the actual being of the thing. Upon its being expressed, the thing’s self enters a realm o f light, and man perceives it because he is "radically and entitively" touched by the one and whole being. The truth of the statement, if we understand it from that original dimensión which makes it possible, is quite cióse to the truth in art. Art is truth in its full execution. The language of art "truthens", its word summons things and invites them to enter "the clearing in the being". When this being is brought forward, we talk about beauty. Beauty is the splendor o f the being’s truth in the hollows of feeling, and this is the most sublime way o f human intellection.